Permanent Female Sterilization in Islamic Jurisprudence and Public Health: A Multi-Perspective Study on Tubectomy - Fahrizen Fahrizen; Syamsu Madyan; Moh. Muhibbin (Bulletin of Indonesian Islamic Studies, 2025)
This study aims to analyze the implementation of tubectomy as permanent contraception from the perspective of maqāṣid al-sharīʿah and international medical standards (WHO and ACOG), focusing on legal legitimacy, medical indications, and patient rights protection. The approach used is juridical-normative with library research. Data were obtained from classical fiqh books, contemporary fatwas, Indonesian reproductive health regulations, and scientific publications related to the effectiveness, risks, and procedures of tubectomy. The analysis was conducted deductively-inductively through the synthesis of maqāṣid principles with clinical evidence and health policies, to formulate Islamic criteria, informed consent procedures, and medical indication verification standards. The research results show that tubectomy is >99% effective but permanent, so it is only permissible under Islamic law in medical emergencies with informed consent and the absence of adequate alternatives. There is a gap between regulation and field practice, particularly in counselling and partner involvement. The recommendations are aimed at integrating medical guidelines and Islamic law for family planning services that are ethical and in accordance with Islamic law. This study contributes by connecting Islamic law and international medical standards to formulate ethical and safe guidelines for tubal ligation practices.